A self-quenching fluorescence probe-mediated exponential isothermal amplification system for highly sensitive and specific detection of microRNAs. Issue 94 (17th November 2021) - Zhao, Jun; Wu, Jiandong; Wu, Xiaosong; Deng, Guoqing; Liu, Yong; Lin, Francis; Zhu, Ling
Abstract : A novel self-quenching fluorescence probe-mediated isothermal amplification system was developed, making highly sensitive and specific detection of miRNAs feasible. Abstract : We designed an efficient self-quenching fluorescence probe and constructed this probe-mediated exponential isothermal amplification system for miRNA detection. Owing to the significant improvement in the detective signal-to-background ratio, a wide dynamic range of 9 orders of magnitude and a limit of detection as low as 0.08 aM can be easily achieved in a single step. Furthermore, benefiting from the additional advantages of high specificity and biocompatibility, the proposed method has been demonstrated to be capable of accurately quantifying miRNA biomarkers in serum, which will provide promising perspectives for clinical diagnosis.